“ANTHROPOHOLISM” AS AN AUTHENTIC TOOL FOR ENVIRONMENTAL MANAGEMENT - Bassey, Samuel Akpan (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
Ever since nonhuman entity and the environment became a major ethical issue, anthropocentric worldviews have been blamed for all that is morally wrong about our dealings with nature. Those who regard themselves as non-anthropocentrists / holistic scholars typically assume that the West’s anthropocentric axiologies and ontologies stir all of the environmental degradations associated with human species. In contrast, a handful of environmental philosophers aver that anthropocentrism is entirely acceptable as a foundation for environmental ethics as human’s perspective cannot be entirely removed from the decision-making process. They often argue that is it possible for the man to act responsibly towards the environment for human’s sake and its future generation. Thus there is an ever-present tension between anthropocentrism and holism, with each side trying to oust talk each other. In my opinion, those extreme views are lump sided, as such lack room for tolerance. The thrust of this paper is to bridge the gap within these ethical theories with the theory of “anthropoholism”. Anthropoholism is a theory in environmental ethics that acknowledges man (anthropo) central role; perspective, place in eco-system as well as ontology but argues that despite this position, Man is just a part of nature, such that he cannot exist independently of the environment, or cannot be understood without reference to the environment. With this, the theory of anthropoholism is able to bridge the gap between the two extreme views by stating the obvious and explaining the connection between the two extreme views.